The regulation of the National Education System (NES) in Brazil: a long debate (Práxis Educativa, 2023)
In this article, it was sought to analyze the debate on the regulation of the National Education System (NES) based on the discussion on the creation of national systems for social policies. In this sense, the ideas related to the federative coordination in Education and the proposals for regulation of the NES were analyzed, including the proposal under discussion in the National Congress. The idea was to discuss the trajectory of this debate, which factors were important in this process and the advances of the current proposals of the system for the federative cooperation. For that, the article presents a qualitative methodological approach, based on a literature review and analysis of secondary data, including technical documents, research reports, bills and regulations. The analysis shows that the ideas present in the Manifesto dos Pioneiros da Educação Nova (Manifesto of the Pioneers of the New Education) and the construction of systems in other policies, as well as changes in the federative coordination after the Federal Constitution of 1988 influenced the continuity of the system in the educational debate and proposals on the NES. However, the delay in approving the system results from the lack of consensus among the actors on how the system should be organized.Keywords: National Education System. Coordination and cooperation. Interfederative relations.